Are Young US Adults Meeting the National Academy of Medicine Recommendations for Adequate Water Intakes? Analyses of NHANES 2011–16 Data. (29th May 2020) - Barrios, Pamela; Vieux, Florent; Maillot, Matthieu; Rehm, Colin; Drewnowski, Adam
Abstract: Objectives: Young US adults consume inadequate amounts of recommended food groups, including fruit, vegetables, and whole grains but little is known about their fluid consumption. The present study aimed to evaluate if this population is meeting the recommendations for adequate fluid intake issued by National Academy of Medicine (NAM). Methods: Beverage consumption data for 2160 adults aged 18–24y came from two 24 h dietary recalls in the three most recent cycles of the United States National Health and Nutrition Examination Survey (NHANES 2011–16). Water intakes (in mL/d) from drinking water, other beverages and moisture from foods were analyzed in relation to the current NAM Adequate Intake (AI) thresholds (3700 mL/d for males and 2700 mL/d for females). The proportion of young adults adhering to the AIs for total water intake was assessed using the National Cancer Institute method for estimating usual intake distributions. Additional analyses examined adherence by gender, income-to-poverty ratio and race/ethnicity. Results: Mean water intakes were 2713 mL/d (3003 mL/d for men and 2382 mL/d for women). Of total water, 1191 mL/d (44%) came from drinking water, tap and bottled; 947 mL/d (35%) from non-water beverages; and 575 mL/d (21%) from foods. Only 35.3% of young adults met the AI recommendations. Female young adults were significantly more likely to meet the recommendations than males (37.8% vs. 29.6%; P  = 0.04). Compared to the other race/ethnicity groups, non-Hispanic white young adults were most likely to meet recommendations (41.5%). Compared to non-Hispanic white young adults, non-Hispanic black young adults were least likely (18.7%, P  < 0.001) to meet recommendations. Mexican-American (29.3%) and other Hispanic young adults (32.3%, P  < 0.05 for each) were also less likely to meet recommendations when compared to non-Hispanic white young adults. No significant effects by family income were observed. Conclusions: Less than half of all young adults and only 18.7% of non-Hispanic Black young adults met the AI recommendations for water. Understanding the reasons for the high proportion of young adults failing to meet recommendations should be the subject of future research. Given the impact of habitual fluid intake on health outcomes, adequate hydration among young adults remains a cause for concern. Funding Sources: Data analyses were sponsored by PepsiCo Inc.